The Effect Of Increasing Telecommunication Network And Internet Availability On The Number Of Domestic Tourists In Indonesia - Pradnyasari, Ida Ayu Putu Ratih; Wildani, Muhammad Alfan; Sri Hartini, Sri (SEIKO : Journal of Management & Business, 2023)
The progression of time and the growing impact of globalization across the globe have generated a demand for a diverse array of technologies, electronic products, and the Internet of Things (IoT). The human requirement for this encompasses various activities, including personal, economic, and numerous other endeavors. Among the sectors, the industrial domain stands out due to its intimate connection with the presence of infrastructure and amenities that guarantee the fulfillment of requirements for technology, electronic commodities, and the Internet of Things (IoT), all of which serve as catalysts in the tourism industry. This is substantiated by the research findings concerning the impact of the independent variables (Telecommunication Network and Internet) on the dependent variable (Number of Domestic Tourists in the Archipelago), revealing a statistically significant correlation of 70.1%. This means that the independent variable can explain the dependent variable well in this study. Additionally, the calculated F value is 154.442 with a significance level of 0.000, which is less than 0.05. Therefore, the model can be used to predict the number of domestic tourists. The results of the regression output indicate that the network coefficient has a value of 17,025.865. This implies that for every one-point increase in the independent variable, the dependent variable is expected to increase by 17.025.865 units. Since the regression coefficient is positive, it can be concluded that the direction of influence of the independent variable on the dependent variable is positive.